Faktor-Faktor Yang Memengaruhi Komitmen Organisasi Melalui Kepuasan Kerja Sebagai Mediasi - Ramadhania, Rezeta Novwan; Wardy, Andes; Nurwanti; Tjahjadi, Karel (Media Bisnis, 2025)
This study aims to find out how person–job fit, work-life balance, and working conditions affect organizational commitment through job satisfaction as a mediating variable. This type of research is descriptive and causal, which is a method of analyzing causal relationships between variables. The total population in this study was 186 employees of PT. Padma Soode Indonesia, with 135 employees being used, selected using purposive sampling techniques. This study used a quantitative approach with a method of collecting data using questionnaires and then analyzed with a licert scale.Data analysis is carried out using Partial Least Square (PLS) techniques in the Smart PLS 4.0 application. Results showed that person–job fit, work-life balance, and working conditions had a significant effect on organizational commitment and job satisfaction. Job satisfaction also has a significant effect on organizational commitment. The role of job satisfaction as a mediation on the influence between person–job fit, work-life balance, and working conditions on organizational commitment has been shown to mediate significantly.